Global response to physiotherapy services disruptions during the COVID-19 pandemic and the level of preparedness for the next health emergency - Kosakowski, Heidi; Skelton, Peter; De Groote, Wouter; Kruger, Jonathon; Salio, Flavio (Frontiers in Rehabilitation Sciences, 2025)
IntroductionThe COVID-19 pandemic was a global health emergency that severely impacted physiotherapy and other rehabilitation services. The purpose of this study is to describe mitigation strategies developed for physiotherapy service disruptions during the COVID-19 pandemic and the level of integration of physiotherapy services into health emergency preparedness planning in countries/territories of World Physiotherapy member organisations.MethodsThe 2022 World Physiotherapy annual membership census (AMC) included questions on health emergency preparedness planning and mitigation strategies in line with WHO recommendations. Quantitative analysis was conducted on response frequencies and disaggregated into World Physiotherapy regions and country/territory income level classifications.Results116 out of 125 World Physiotherapy member organisations (MOs) participated in the census. 24% of all participating MOs reported not adopting any of the listed mitigation strategies to overcome physiotherapy service disruptions in their country/territory during the COVID-19 pandemic. 64% of participating MOs reported that physiotherapy services were not included in any health emergency preparedness component for rehabilitation in their country/territory.DiscussionThere are low levels of integration of physiotherapy services into national and subnational health emergency preparedness planning. A country's income level does not appear to be a major determinant of emergency preparedness.